The Relationship Between Parents' Communication Patterns and Development In Pre-School Children (Kb-Tk) Tbs Kajan, Krandon Kudus - Anggi Zahra Saputri; Umi Faridah; Sukesih (CV. Inara, 2026)
The research method used was quantitative with a correlative descriptive design and a cross-sectional approach. The research sample amounted to 66 children aged 4–5 years who were selected using the purposive sampling technique. The research instruments were a questionnaire on parental communication patterns and the Denver Developmental Screening Test (DDST). The results of the study showed that most parents have good communication patterns and the majority of children are in the normal developmental category. The statistical test showed a p-value of 0.000 (p < 0.05), which indicates a significant relationship between parental communication patterns and preschool child development. The conclusion of this study is that parental communication patterns have an important role in supporting the optimal development of preschoolers. Open, empathetic, and responsive communication patterns are able to create positive stimulation for children so that children's development can take place comprehensively and continuously. Therefore, parents are expected to continue to improve the quality of communication with children as an effort to support optimal children's growth and development.